Arginase: da imobilização à modulação de ensaios de afinidade em coleções de produtos naturais - Costa, Romário Pereira da (2019)
ARGINASE: FROM THE IMMOBILIZATION TO MODULATION OF AFFINITY ASSAY IN COLLECTIONS OF NATURAL PRODUCTS. The use of natural products from plants dates from antiquity and they are often targets as they exhibit biological properties of interest for new drug discovery. Unfortunately screening natural products for biologically active compounds, is laborious, time consuming and Costly. To meet this end, new affinity assay model based on the use immobilized protein have developed and it was the objective of this work. This work consisted of the immobilization of arginase on to magnetic beads (Arg-MBs) for screening of natural products extracts. The modulation of the assay was initially carried out for the compounds: catechin and epicatechin (reported as arginase inhibitors) and as negative control (not inhibitor), acyclovir. For the assays, two ethanolic extracts were selected: Byrsonima coccolobifolia (Malpighiaceae) and Tabebuia ochracea (Bignoniaceae). From the leaves extract of Byrsonima coccolobifolia (Malpighiaceae) 12 ligands were identified, and 9 of these characterized by LC-HRMS. While from crude ethanolic roots extract of Tabebuia ochracea (Bignoniaceae) nineteen ligands were fished out. For chemical elucidation, these compounds need to be isolated in milligram scale. The number of ligands identified in the two ethanolic extracts showed the potential of the affinity assay developed. The development of the assays, results and studies for structural elucidation of the ligands identified will be discussed in detail in this dissertation.